Redundant Configuration of Automated Flow Lines. Issue 12 (2016) - Müller, Christoph; Grunewald, Martin; Spengler, Thomas S.
Abstract: Robot failures are a significant challenge in the operation of automated flow lines since they result in throughput losses due to blocking and starvation of upstream and downstream stations, respectively. To some extent, these throughput losses can be reduced by installing buffers between the stations. However, the installation of buffers requires considerable investments and scarce factory space. With the emergence of advanced robotics and autonomous transportation units flow lines become increasingly flexible. This opens up new solutions to reduce throughput losses caused by failures. One solution is a redundant configuration, in which downstream stations automatically take over the tasks of failed stations and therefore make the line more robust against failures. The throughput loss in these situations mainly depends on the level of redundancy designed into the system. The focus of this contribution is set on a mathematical formulation to balance flow lines under consideration of redundancies. The developed approach maximizes the lines' level of redundancy for a given number stations. In a numerical analysis we demonstrate the effectiveness of the approach and show that redundant configurations lead to an increase of average throughput rates.